Legitimation in discourse: The case of women subjected to violence - Badia Elharraki (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
This article attempts to analyze the discourse of women subjected to marital violence. In this regard, we will analyze how these women legitimize their discourse through evaluation as a narrative component and as a strategy that aims to establish a mode of argumentation that victimizes them and demonizes the violent husbands. The site from which the data is extracted is a TV talk show “Qesset Nnass” (The story of people) on the Moroccan TV channel Medi 1 TV. Specifically, we will be concerned with the ways women articulate propositions through moral legitimation to send messages that can only be decoded by reference to the cultural variable of language. The stories scrutinized are significant in that they foreground the extreme suffering women are subject to within a patriarchal society that leaves no room for acceptable alternatives at the economic, legal, and social levels.